Utilization of zakat fund for social development: reading from Islamic wealth management perspective - Zakariyah, Habeebullah; Kehinde, Lawal; Hassan Habeebullahi, Bature (USIM, 2019)
The modern propose system of zakat institution is very important for promoting economic and social instrument tools for the poverty eradication and economic stability in Muslims societies. This paper aims to examine the impact of social responsibility of financial performance, eradication of poverty and economic distribution of wealth in the modern world by using zakat fund as a measure. The main objective of this study is to examine to what extent zakat fund can be utilized for the economic growth and social development of the Muslims societies. Zakat being the third pillars of Islam, has a great significant and substantial role to play in wealth management and economic development particularly in the area of human capital empowerment for the long term rather than short term relief for the poor people and other categories mentioned in the Qur’an (asnaf), this will prevent zakat fund from being diverted for other purposes rather than its main objective (Maqasid of Zakat). A critical analytical approach has been adopted in conducting this study. Finally, this paper concluded that Zakat funds can be used for capital investment in providing assistance for the needy people (Asnaf) which will have long term social impact to improve the standard living of people.